Fumaric acid esters in combination with a 6‐week course of narrowband ultraviolet B provides an accelerated response compared with fumaric acid esters monotherapy in patients with moderate‐to‐severe plaque psoriasis: a randomized prospective clinical study. (1st March 2018) - Tzaneva, S.; Geroldinger, A.; Trattner, H.; Tanew, A.
Summary: Psoriasis is a chronic recurring inflammatory skin condition with a significant impact on patients' quality of life. It affects about 2–3% of the population in Western countries and is due to a dysregulation of the immune system. The cause and development of psoriasis is complex and involves both genetic and environmental factors. Plaque psoriasis is the most common type of psoriasis and causes raised red skin lesions with a silvery white flaky surface. There is no cure for psoriasis but current treatments can hold symptoms at bay. Fumaric acid esters (FAE) are amongst the first‐line treatments in European countries where this medication is available. FAE are effective and generally safe but take a while to start working. A short‐term combination with narrow‐band ultraviolet (NB‐UVB) phototherapy might overcome this drawback and help to accelerate the response in the early stage of treatment. Our randomized controlled prospective trial was designed to investigate whether an initial addition of NB‐UVB to FAE improves the clinical response and quality of life in patients with plaque psoriasis. The researchers who performed this study are based at the Department of Dermatology, Medical University of Vienna, Austria. The patients were randomly (by chance) assigned to two treatment groups: one group received treatment with FAE alone and the second group received a combination of FAE and a 6‐week course of narrow‐band UVB. We found that adding a short course of NB‐UVB to FAE both accelerated and improved the clearing of psoriasis and the patients' quality of life.